Effects of the telescopic seismic dissipper in front of the structural behavior of social buildings in the Huaraz Independence district - Maza Rubina, Arturo Esaquiel (2020)
The present article exposes the development of the investigation of the seismic energy dissipators of the telescopic type, in the structural behavior of the social constructions in the district of independence, province of Huaraz-Ancash. The analysis of a building for social housing of 3 to 4 floors will be carried out for the two structural systems, that is, with a conventional structure and the other with hysterical seismic dissipators for which, maximum displacements, accelerations and efforts in harder areas of the structure. The energy dissipation capacity of the dynamic systems studied will be determined, emphasizing the modal response of buildings with installed heatsinks.